2023
DOI: 10.21203/rs.3.rs-2069710/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood-brain barrier disruption in Long COVID-associated cognitive impairment

Abstract: Vascular disruption has been heavily implicated in COVID-19 pathogenesis and may predispose the neurological sequelae associated with the condition now known as long COVID. To date, no studies have objectively assessed blood-brain barrier (BBB) function in individuals with neurological complications stemming from prior SARS-CoV-2 infection. Here, we explored the neurobiological effects of SARS-CoV-2 infection in humans with acute infection (n = 76) and those with persistent long COVID with and without neurolog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Like D-dimer, factor V is more active in patients with severe COVID-19, which associated with venous thromboembolism 34 . Neural imaging studies now confirmed patients with SARS-CoV-2 infection have much increased brain vascular permeability based on Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) 35 . While all these evidence points to a critical role of cerebrovascular dysfunctions in the development of neurological manifestations associated with COVID-19, our basic understanding of the cellular and molecular changes in the brain vasculature remains limited.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Like D-dimer, factor V is more active in patients with severe COVID-19, which associated with venous thromboembolism 34 . Neural imaging studies now confirmed patients with SARS-CoV-2 infection have much increased brain vascular permeability based on Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) 35 . While all these evidence points to a critical role of cerebrovascular dysfunctions in the development of neurological manifestations associated with COVID-19, our basic understanding of the cellular and molecular changes in the brain vasculature remains limited.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence from the hACE2 transgenic mouse model that is susceptible to SARS-CoV-2 infection indicated that SARS-CoV-2 may be able to pass the BBB with the help of angiotensin-converting enzyme 2 (ACE2) receptor, without causing significant damage to the BBB integrity 20 . Yet, human post-mortem studies 13 and neural imaging follow-up in COVID-19 patients 35 , and in vitro cell models 36 indicated that BBB dysfunction may be an important aspect. Mechanistically, Jan Wenzel et al even reported that SARS-CoV-2 protease Mpro can cleave NEMO and impair nuclear factor-κB in brain endothelial cells 37 , and causing endothelial changes in mouse model of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…34 Neural imaging studies now confirmed patients with SARS-CoV-2 infection have much-increased brain vascular permeability based on dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). 35 While all the evidence points to a critical role of cerebrovascular dysfunctions in the development of neurological manifestations associated with COVID-19, the understanding of cellular and molecular changes in the brain vasculature remains limited. Thus, our studies provided clear evidence of the cerebrovascular injury and barrier dysfunctions post-severe SARS-CoV-2 infection and highlighted the cellular and molecular events that drive the breakdown of the BBB and BCSFB, including tight junction loss, pericyte damage, endothelial activation, vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the hACE2 transgenic mouse model that is susceptible to SARS-CoV-2 infection indicated that SARS-CoV-2 may be able to pass the BBB with the help of ACE2 receptor, without causing significant damage to the BBB integrity. 20 Yet, human postmortem studies 13 and neural imaging follow-up in COVID-19 patients, 35 and in vitro cell models 41 ChP cells also express ACE2 and were proposed as an alternative route of SARS-CoV-2 neuroinvasion. 43 This was further confirmed using ChP organoids, showing SARS-CoV-2 not only infected these organoids but also entered the ventricular CSF compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation